In decem mensibus gigni hominem - Zabłocki, Jan (Prawo Kanoniczne, 1992)
Noctes Atticae of Aulus Gellius is a collection of memoranda of a most miscellaneous description, dealing with literatury and grammatical criticism, philosophy, law, history and antiquarian topies. In 3. 16 there are references to the variation in the periods of gestation reported by physician and philosophers; moreover incidentally, to the views also of the ancient poets on that subject many other noteworthy and interesting particulars. To legal students the interest of this book of Aulus Gellius lies chiefly in the references contained therein to the ius trium liberorum and the provision of the XII Tables that a child is born in ten months and not in the eleventh month.